Measurement of the school climate in district educational institutions of Bogotá through virtual tools according to the perception of the students (Memorias Sifored - Encuentros Educación UAN, 2021)
Design a virtual system for measuring the school climate in Bogotá's IEDs, based on the perception of students in cycles three and four.
Keywords: measurement; school climate; Bogotá; virtual tool; students perception